Experimental study on the mechanical properties and microstructure of chopped basalt fibre reinforced concrete - Jiang, Chaohua; Fan, Ke; Wu, Fei; Chen, Da (Materials in engineering, 2014)
•Effect of volume fraction and length of basalt fibre on concrete properties is tested.•Adding basalt fibre is found to improve mechanical properties of concrete.•A good bond between basalt fibre and matrix interface is observed in the early age by SEM.•MIP analysis shows basalt fibre concrete presents higher porosity. With high ductility and sufficient durability, fibre reinforced concrete (FRC) is widely used. In this study, the effects of the volume fraction and length of basalt fibre (BF) on the mechanical properties of FRC were analyzed. Coupling with the scanning electron microscope (SEM) and mercury intrusion porosimeter (MIP), the microstructure of BF concrete was studied also. The results show that adding BF significantly improves the tensile strength, flexural strength and toughness index, whereas the compressive strength shows no obvious increase. Furthermore, the length of BF presents an influence on the mechanical properties. Compared with the plain concrete, the compressive, splitting tensile and flexural strength of concrete reinforced with 12mm BF increase by −0.18–4.68%, 14.08–24.34% and 6.30–9.58% respectively. As the BF length increasing to 22mm, corresponding strengths increase by 0.55–5.72%, 14.96–25.51% and 7.35–10.37%, separately. A good bond between the BF and the matrix interface is observed in the early age. However, this bond shows degradation to a certain extent at 28days. Moreover, the MIP results indicate that the concrete containing BF presents higher porosity.